Reimagining the cycle: interaction in self-tracking period apps and menstrual empowerment - Tylstedt, Beatrice; Normark, Maria; Eklund, Lina (Frontiers in Computer Science, 2023)
FemTech, technology often in the forms of apps developed to specifically target female health issues, have billions of users globally. Yet, despite the popularity of e.g. period trackers or pregnancy apps, we know little about the potential impact of these technologies, often developed outside controlled and regulated healthcare. How interactive technology is designed, and in our case the cycle represented through the design, has the potential to shape women's understanding of menstruation. In this study we analyse the interface design of nine of the most downloaded menstruation apps, asking how commercial menstruation apps represent the cycle through their interaction design. While previous research has criticised these types of apps for lacking privacy and for enforcing normative ideals on women, they are often marketed in terms of female empowerment. However, the term 'empowerment' is today used broadly and is known for having many potential meanings. Even within the field of Human Computer Interaction (HCI), 'empowerment' is used frequently but rarely explicitly defined. The question then becomes what empowerment could mean for menstruation tracking. In order to begin exploring the way menstruation and the period is represented in current apps and the way that future apps could design for empowerment, we engage in a comparative design investigation using what we call critical appwalkthrough methodology where an app's design is explored comprehensibly at one point in time and apps interacted with over a longer time period through researcher use-diares. Our results centre around three ways in which these apps represent the cycle to users through design. We analyse; 1) interface metaphors used to represent the temporality of bleeding, 2) datafication of menstruation through input and output for intimate data tracking, and 3) the ways fertility predictions convey certainty over uncertainty. In a second step, we then explore what empowerment could mean for period trackers and how design could support both individual and group empowerment. Finally, we present four design sensitivities meant to inspire designers to design for other types of period tracking experiences that might better empower bleeders. These are: support lived temporalities, embrace uncertainty, empower the self, and design less.